GAMIFICATION AND MOTIVATION: TRANSFORMING LEARNING IN THE DIGITAL UNIVERSITY - Mudryi, Yaroslav; Mudra, Olena (SWorld-Ger Conference proceedings, 2025)
The article examines the influence of gamification on student motivation and engagement within the context of digital higher education. The theoretical basis is the Self-Determination Theory (SDT), which explains how gamified elements address students’ ne